Innovative Barn Cattle for Microclimate Management through the Misting System - koekoeh santoso; Rani Audona; komariah komariah; Kudang Boro Seminar; Mokhamad Fakhrul Ulum (Buletin Peternakan, 2023)
Cattle is meat-producing livestock of the large ruminant. The environmental conditions must remain in the thermoneutral zone because this affects livestock productivity. An environmental modification related to microclimate management is required through a misting system using a water sprinkler. The study was conducted in one of the barns of the Sekolah Peternakan Rakyat (SPR) Maju Bersama livestock group in Drokilo Village, Kedungadem District, Bojonegoro Regency, East Java. The purpose of this study was to analyze the microclimate management of the barn through the misting system in order to improve the physiological response of cattle. The variables observed were the air temperature, air humidity, Temperature Humidity Index (THI), respiratory frequency, heart rate, rectal temperature, and body surface temperature. Body surface temperatures were measured on the face, back, and rump. The analytical method used in this was unpaired T-test five replications. The results showed that the average microclimate data for barn cattle were: air temperature 27.40±0.59°C, air humidity 83.92±1.55%, and Temperature Humidity Index (THI) 79.59±1.06. The results showed that the average physiological response data for cattle were: heart rate 47.02±2.29 beats per minute, respiration rate 16.94±1.26 beats per minute, and rectal temperature 38.65±0.27°C. The results showed that the average body surface temperature data for the face was 37.03±0.38°C, the back was 36.33±0.59°C, and the rump was 36.28±0.68°C. The results showed that the treatment before and after the morning measurement water misting was significantly different (p<0.05) in all the observed variables. Water misting has the effect on decreasing the air temperature, humidity, Temperature Humidity Index (THI), respiratory rate, heart rate, body temperature, and rectal temperature.